The European Union’s Support to the Pan-African Parliament in Achieving Legislative Authority - Mohamoud, Ahmed Madey (Multidisciplinary Journal of Horseed International University (MJHIU), 2025)
This article investigates the significant role played by the European Union (EU) in supporting the Pan-African Parliament (PAP) as it strives to gain legislative powers in addition to the advisory role within the framework of the African Union (AU). Pan African Parliament founded in 2004, and has been designed to serve as a platform for representing the interests and voices of African citizens in the AU’s governance processes, which not only fosters democratic engagement, but inclusive decision-making across the continent as well. Despite these aspirations, PAP has remained limited to an advisory role, without the legislative authority necessary to implement or enforce policies at a continental scale.